It is all about desires! Motivation to engage in medical tourism practices and subjective well-being. - Loureiro, S. M. C.; Panchapakesan, P. (Proceeding of 2016 GAMMA-Global Marketing Conference -Bridging Asia and the World: Global Platform for interface between Marketing and Management, 2016)
Medical tourism has becoming a topic of increase interest for both researchers and practitioners all around the world. The current article intends to propose a conceptual framework that presents antecedents and outcomes of consumers (patients) desires to undergo medical tourism practices, as well as moderators that can strengthen or weaken the established relationships. In the future the model should be tested in cross cultural context and so contribute to give more insights for researchers and mangers of medical tourism.